Залежність будови поверхні терморозширеного графіту від способу його одержання - Sidorenko, I. G.; Ogenko, V. M.; Zagorovsky, G. M.; Prikhod'ko, G. P.; Yanchenko, V. V. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2003)
A difference between surface structure of thermoexfoliated graphite, which have been prepared of graphite bisulfate that was synthesized by chemical and electrochemical methods has been shown by the methods of thermogravimetry, X-ray photoelectron spectroscopy, and electron microscopy. A formation has been proved of bonds between carbon and sulfur atoms in thermoexfoliated graphite that was prepared by electrochemical method employed.